Identification of a novel effector gene and its functional tradeoff in Fusarium oxysporum f. sp. cepae that infects Welsh onion. (January 2023) - Sakane, Kosei; Akiyama, Mitsunori; Ando, Ayaka; Shigyo, Masayoshi; Ito, Shin-ichi; Sasaki, Kazunori
Abstract: Fusarium oxysporum f. sp. cepae ( Foc ) is a causal agent of Fusarium wilt in Welsh onion, leading to tremendous production loss. However, pathogenicity-related factors in Welsh onion-infecting Foc have not been elucidated. Here, we screened F. oxysporum f. sp. C epae E ffector candidate P rotein ( Cep ) from next-generation sequencing data of Welsh onion-infecting Foc . Intriguingly, most of the Cep genes (including SIX2 and SIX9 ) expressed during infection were located on a 3-Mb-sized chromosome in Welsh onion-infecting Foc . Further investigation of the 3-Mb-sized chromosome clarified that the Cep28 is related to virulence, pigmentation, vegetative growth, and stress tolerance and has a functional tradeoff between virulence and vegetative growth. Highlights: Foc that exhibits high virulence in Welsh onion possesses SIX2 and SIX9 genes. Effector-like genes are intensively located on the 3-Mb-sized chromosome in Foc. Cep28 has a functional tradeoff between virulence and vegetative growth.